School discipline, school uniforms and academic performance. Issue 6 (8th August 2016) - Baumann, Chris; Krskova, Hana
Abstract : Purpose: The purpose of this study was to examine the role of school discipline in achieving academic performance. The study aims to clarify the role of permissive vis-à-vis authoritative teaching styles with an overarching hypothesis that better discipline leads to better academic performance. We also probe whether uniformed students have better discipline. Design/methodology/approach: We analyse OECD's Programme for International Student Assessment (PISA) data on school discipline dimensions: students listening well, noise levels, teacher waiting time, students working well, class start time. ANOVA with post hoc analysis on five geographic groups established by Baumann & Winzar (2014) was applied to test for geographic differences (Europe, Americas, Far East Asia, Rest of Asia, Anglo-Saxon cluster) in school discipline. ANOVA was further used to test for school discipline and academic performance. Thirdly, t-tests on five discipline dimensions were run to test for differences between students who wear uniforms and those who do not. Findings: The results demonstrate differences in school discipline across five geographic clusters, with East Asia leading the way. We demonstrate significant differences in discipline for low, medium, and high performing students. Peak-performing students have the highest level of discipline. Students wearing a uniform listen better with lower teacher waiting times. Originality/value: Students peak perform when teachers create a disciplined atmosphere where students listen to teachers, where noise levels in the classroom are low and they do not have to wait to start class and teach. Good discipline allows students to work well and this ultimately leads to better academic performance. Uniforms contribute to better discipline in every day school operations. Our findings support that in general, implementing school uniforms at schools might enhance discipline and allow for better learning. We recommend keeping uniforms where they are already used and to consider introducing uniforms where they are not yet common.